Myasthenic Crisis in an Elderly Patient with Positive Antibodies against Acetylcholine and Anti-MuSK, Successfully Treated with Noninvasive Mechanical Ventilation - José A. Fernández; Antonio Fernández-Valiñas; Daniel Hernández; Joel Orozco; Antonio Lugo (Case Reports in Critical Care)
Myasthenia gravis is an autoimmune disease characterized by muscle weakness. Subjects with antibodies against acetylcholine usually have greater ocular symptoms, lower bulbar weakness, and fewer respiratory complications, compared to individuals with anti-MuSK antibodies. The presence of positivity to both types of antibodies in the same patient is uncommon, and the clinical behavior of these individuals is uncertain. A myasthenic crisis is characterized by respiratory and bulbar muscle weakness, causing acute respiratory failure which requires mechanical ventilatory support. We present the case of a 73-year-old man with a medical history of myasthenia gravis and positive antibody titers against acetylcholine and anti-MuSK, who sought for medical assessment because of respiratory tract infection symptoms, dysphagia, and generalized weakness. Initially, no respiratory distress was found. After 24 hours the patient showed respiratory deterioration and neurological impairment. Endotracheal intubation was rejected, so ventilatory support with noninvasive ventilation was started. The patient was supported by intense respiratory therapy, and infusion of immunoglobulin was initiated. The individual responded favorably, improving his general condition. Weaning from noninvasive mechanical ventilation was possible after six days. Our case illustrates that noninvasive ventilation, properly supported by intense respiratory therapy, can be a great option to avoid intubation in the myasthenic patient.